Numerical Simulation of Finite Deformations of a Dynamically Loaded Elasto-Viscoplastic Circular Membrane - Dornowski, W. (Engineering Transactions, 2003)
The present paper deals with theoretical modelling and numerical simulation of a thin circular plate subjected to impulsive loading. To this end, the convective description is applied. The kinematical hypothesis used for theoretical description of the transient response includes membrane deformations only. This assumption is valid in the range of large deformations. The dynamical response of the material is described by Perzyna's elasto-viscoplastic constitutive relations. The theory is completed by an algorithm of the explicit finite difference method. With respect to the conditional stability of that method, the stability criterion is given. Basing on experimental data, an identification of material parameters is carried out. Some comparisons with the corresponding theoretical and experimental results are presented. Satisfactory agreement of the results has been found. Finally, an example of the plastic strain localization in a membrane is presented.